2016
DOI: 10.20517/2347-8659.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Serum immuno-biomarkers in gliomas

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Using a cutoff value of NLR<4.7, both overall survival (OS) and progression-free survival (PFS) were significantly longer. This study supports another work [2,16] which also revealed NLR as an independent prognostic marker, using a cut-off value of 4, and is consistent with other studies demonstrating the prognostic value of NLR in other tumor types [2,17,18].…”
Section: Need For Diagnostic Biomarkers For Gliomasupporting
confidence: 92%
See 4 more Smart Citations
“…Using a cutoff value of NLR<4.7, both overall survival (OS) and progression-free survival (PFS) were significantly longer. This study supports another work [2,16] which also revealed NLR as an independent prognostic marker, using a cut-off value of 4, and is consistent with other studies demonstrating the prognostic value of NLR in other tumor types [2,17,18].…”
Section: Need For Diagnostic Biomarkers For Gliomasupporting
confidence: 92%
“…This is why invasive glioma has a low cure rate and a high recurrence rate. In this direction, a promising new tool to combat GBM is immunotherapy, which has emerged from intensive research, revealing that although highly immunogenic, it actively suppresses the host anti-tumoral immune response through a number of mechanisms [2,12,13]. A deeper understanding of specific molecular markers is the core part of such immunotherapy.…”
Section: Need For Diagnostic Biomarkers For Gliomamentioning
confidence: 99%
See 3 more Smart Citations